1997
DOI: 10.1128/jb.179.15.4942-4945.1997
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of the phosphoenolpyruvate carboxylase gene from the purple nonsulfur bacterium Rhodopseudomonas palustris No. 7

Abstract: The ppc gene, encoding phosphoenolpyruvate carboxylase (PEPC), from Rhodopseudomonas palustris No. 7 was cloned and sequenced. Primer extension analysis identified a transcriptional start site 42 bp upstream of the ppc initiation codon. An R. palustris No. 7 PEPC-deficient strain showed a slower doubling time compared with the wild-type strain either anaerobically in the light or aerobically in the dark, when pyruvate was used as a carbon source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 24 publications
3
27
0
Order By: Relevance
“…It is also possible that intracellular CA aids in the conversion of CO # to HCO − $ for fixation by phosphoenolpyruvate carboxylase . Both biochemical pathways are found in photosynthetic bacteria (Buchanan et al, 1967 ;Inui et al, 1997 ;Tabita, 1995) although carboxysomes are not found in PNSB and our results suggest that CA enzyme is not associated with RubisCo, because the main CA activity was found in the periplasmic fraction. Periplasmic localization and the presence of the enzyme only under anaerobic conditions suggests that CA participates in C i utilization in this bacterium.…”
Section: Localization and Expression Of Casupporting
confidence: 55%
“…It is also possible that intracellular CA aids in the conversion of CO # to HCO − $ for fixation by phosphoenolpyruvate carboxylase . Both biochemical pathways are found in photosynthetic bacteria (Buchanan et al, 1967 ;Inui et al, 1997 ;Tabita, 1995) although carboxysomes are not found in PNSB and our results suggest that CA enzyme is not associated with RubisCo, because the main CA activity was found in the periplasmic fraction. Periplasmic localization and the presence of the enzyme only under anaerobic conditions suggests that CA participates in C i utilization in this bacterium.…”
Section: Localization and Expression Of Casupporting
confidence: 55%
“…Assays for GAPDH (Omumasaba et al, 2004), phosphoglycerate kinase (PGK) (Eikmanns, 1992), triosephosphate isomerase (TPI) (Eikmanns, 1992), PEPC (Inui et al, 1997) and LDH (Bunch et al, 1997) were performed as previously described. Malate dehydrogenase (MDH) activity was determined as described by Sridhar et al (2000), modified by using 0.1 M Tris/HCl (pH 8.0) and 0.15 mM NADH to obtain optimum enzyme activities.…”
Section: Methodsmentioning
confidence: 99%
“…Under anaerobic conditions in the light, all species grow photoheterotrophically when supplied with various organic substrates or photoautotrophically with CO 2 as a sole carbon source. Under microaerobic to aerobic conditions in the dark, many representatives can grow chemoheterotrophically, and some grow chemoautotrophically (40).To develop a new CO 2 -fixing bioprocess, we have been performing biochemical and genetic analyses of intermediary metabolism, including CO 2 fixation, underlying the complex modes of growth in the PNSB, using Rhodopseudomonas palustris as a model microorganism (4,23,24). For this purpose, development of a versatile host-vector system would be helpful.…”
mentioning
confidence: 99%
“…To develop a new CO 2 -fixing bioprocess, we have been performing biochemical and genetic analyses of intermediary metabolism, including CO 2 fixation, underlying the complex modes of growth in the PNSB, using Rhodopseudomonas palustris as a model microorganism (4,23,24). For this purpose, development of a versatile host-vector system would be helpful.…”
mentioning
confidence: 99%
See 1 more Smart Citation